ANALISIS SEKTOR EKONOMI UNGGULAN DAN POTENSIAL TERHADAP PERTUMBUHAN EOKONOMI DI PROVINSI ACEH - Wardatul Husna; Ratna Husein (Jurnal Ekonomi Regional Unimal, 2023)
This  reseach  aims  to  analyze  leading  economic  sectors  and  potential sectors for economic growth in Aceh Province. The analytical method in this reseach uses the Location Quotient (LQ) method, Shift Share method and multiple linear regression models. Partially, the leading sector has a negative and significant effect on economic growth, the potential sector does not have a significant and negative effect on economic growth. Together the leading and potential sectors have a positive and significant impact on economic growth in the Province of Aceh. Recommendations, it is hoped that the Aceh government will see the potential of the leading sector  and  the  potential  of  the  sector  in  its  territory,  so  that  it  can encourage economic growth by exploring the potential that exists in the Province of Aceh.